Electrochemical performance at sputter-deposited nanocarbon film with different surface nitrogen-containing groups. Issue 21 (16th May 2019) - Kamata, Tomoyuki; Kato, Dai; Niwa, Osamu
Abstract : Carbon materials containing nitrogen have been extensively studied as electrode materials for use in non-platinum cathodes of fuel cells due to their high electrocatalytic activity for oxygen reduction. Abstract : Carbon materials containing nitrogen have been extensively studied as electrode materials for use in non-platinum cathodes of fuel cells due to their high electrocatalytic activity for oxygen reduction. The activity is strongly dependent on the structure of surface nitrogen-containing functional groups. Carbon film containing nitrogen is also suitable for analytical applications because of its low background noise and its electrocatalytic activity, which is superior to that of pure carbon film. Here, we fabricated sputter-deposited nanocarbon film with a nitrogen-containing group and estimated the efficacy of a surface nitrogen-containing group for detecting biomolecules. Two types of carbon films, one rich in graphite-like nitrogen-containing bonds and the other rich in pyridine-like bonds, were successfully fabricated without changing their nitrogen concentration, sp 2 /sp 3 ratio or surface flatness. The carbon film rich in pyridine-like bonds shows a positive oxygen reduction peak of about 250 mV compared with pure carbon film and is also 200 mV more positive compared with film with graphite-like nitrogen-containing bonds. This indicates that pyridine-like bonds contribute more effectively to electrocatalytic activity than graphite-like nitrogen-containing bonds. For detecting biomolecules, carbon film rich in pyridine-like bonds also exhibits more negative peak potentials for the oxidation of NADH andl -ascorbic acid, suggesting that carbon film rich in pyridine-like bonds will show improved performance for detecting electroactive biomolecules.